Case report: Diagnosis and intervention of a non-24-h sleep–wake disorder in a sighted child with a psychiatric disorder - Estivill-Domènech, Carla; Rodriguez-Morilla, Beatriz; Estivill, Eduard; Madrid, Juan Antonio (Frontiers in Psychiatry, 2024)
Circadian rhythm sleep-wake disorders (CRSWD) are sleep disfunctions related to its circadian functioning. They are characterized by symptoms of insomnia or excessive sleepiness that occur because the intrinsic circadian pacemaker is not entrained to a 24-hour light/dark cycle. Affected individuals with free-running disorder or hypernycthemeral syndrome (N24SWD) have a longer wake-sleep cycle that produces a sleep pattern that typically delays each day. The disorder is seen in 70% of blind people and among people with healthy vision it is a rare pathology. Among sighted cases, 80% are young males and 28% have a psychiatric disorder.The patient is a 14-year-old boy with a psychiatric pathology diagnosed as a PANDAS syndrome (Pediatric Autoimmune Neuropsychiatric Disorder Associated with streptococci), a sudden acute and debilitating onset of intense anxiety and mood lability accompanied by obsessive compulsive-like issues and/or tics, in association with a streptococcal-A infection that occurres immediately prior to the symptoms. As a comorbidiy, he exhibits severe insomnia due to an irregular sleep pattern, that strongly delays his sleep schedule day to day. It affects to his daily routines, since he is not going to school, and aggravates, furthermore, the psychiatric symptoms. He is referred for the sleep consultation, where the case is explored by ambulatory circadian monitoring (ACM) using the novel system Kronowise® (Chronolab, Universidad de Murcia) and diagnosed with a non-24-hour sleep-wake disorder (N24SWD).The first treatment approach for the patient was focused on improving symptoms during the acute infection and psychiatric symptoms. Additionally, sleep pathology was treated by light therapy and melatonin. After 8 months and different trials, it was possible to establish a treatment to normalize the symptoms and fix his sleep rhythm in a normal schedule as well as to reduce anxious symptoms during the day.The association of PANDAS and N24SWD has not previously been reported in the literature.